USAHA PEMERTAHANAN DAN REVITALISASI BAHASA PONOSAKAN (THE RETENTION AND REVITALIZATION OF PONOSAKAN LANGUAGE) - Asis Kamma (Kadera Bahasa, 2016)
Ponosakan language is an identity of Ponosakan ethnic that lives in North Sulawesi. The language is one of potential culture of treasure in Indonesia. Currently, Ponosakan language entitled as an endangered languange. It is due to several factors, its speakers as well as factor of external of Ponosakan community. Therefore, Ponosakan language needs to be preserved, maintained, and revitalized. For in Indonesia social context, Ponosakan language is one of 746 local languages of Indonesia. The preservation and revitalization efforts need to be done. The efforts need to be adapted to the policy of Indonesian goverment and characteristics of the language itself